THE EFFECT OF PRICE AND PRODUCT QUALITY ON CONSUMER SATISFACTION IN THE CHANG3.ID THRIFTSHOP BUSINESS - Fahmi Zain; Sihabudin; Robby Fauji (Journal Of Resource Management, Economics And Business, 2025)
Purpose: The aim of this research is to determine the effect of price and product quality on consumer satisfaction Research Methodology: This research uses a quantitative approach. Data processing was done using SPSS, and the analysis techniques include path analysis and descriptive analysis. Results: The research results show that price and product quality have a positive influence on Chang3.id consumer satisfaction. Limitations: The study only focuses on one thriftshop, Chang3.id, in Karawang area. Contribution: This study can be useful for thriftshop businesses to understand the importance of pricing and product quality in achieving consumer satisfaction.